'Learning' Development. Issue 1 (2nd January 2018) - White, Pamela; Devereux, Peter
Abstract: How can we prepare for and motivate ongoing improvements in development practice in the world of universal sustainable development goals? International Development Studies courses are a relatively new phenomenon. Earlier, people entered the field with technical backgrounds and learnt on the job. Similarly, many took the road from long-term international volunteering or Junior Expert/Junior Professional Officer posts, and moved into a career in international development [Baillie Smith, M. and N. Laurie, 2011, 'International volunteering and development: Global citizenship and neoliberal professionalisation today', Transactions of the Institute of British Geographers ; Devereux, P., 2008, 'International volunteering for development and sustainability: Outdated paternalism or a radical response to globalisation?', Development in Practice, Vol. 18, No. 3, pp. 357–370; White, P., 2015, 'The spectrum of motivations, experiences and attitudes in technical development cooperation', Forum for Development Studies, Vol. 42, No. 1, pp. 89–112]. More recently, development studies courses have emerged. Are they finding the right balance between critical approaches, history and vocational skills? A difference in motivations and expectations between early and mid-late career Finnish development workers was found from earlier research (White, 2015). With this case study we add a focus on the pre-career stage (via questionnaires and interviews), considering the motivations of Finnish development studies students in first year, postgraduate studies and after graduation. The article acknowledges the range of motivations and experience of those engaged with international development. It also considers the tension between critical theory and vocational skills. Competencies for development practice encompass a combination of theoretical knowledge, technical skills, administrative know-how and attitudinal factors. We conclude that co-production, combining academic courses and research, including reflective and experiential practice, is a positive step forward.